2020
DOI: 10.21608/mvmj.2020.21.313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary probiotic, antibiotic or combination on broiler performance, cecum microbial population and ileal development

Abstract: To investigate the effect of antibiotics and/or probiotics on performance, some serum metabolites, cecum microflora composition, and ileum histomorphology in broilers under the Egyptian conditions. Design: Randomized controlled experimental study. Animals: Two hundred forty 1-day-old Ross (308) chicks were reared till 35 days of age. Procedures: The birds were randomly allocated into four main groups: a control diet without additives (CON); probiotic (Lactobacillus acidophilus) supplemented diet (PRO); antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…In this study, adding probiotics and essential oil led to a significant decrease in these parameters. Similar to previous studies, our results showed that serum total protein and albumin were not affected by dietary supplements 41 , 42 . Furthermore, our results have similarities with Santoso et al 43 who reported that adding probiotics lowered levels of ALT enzyme compared with the control treatment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, adding probiotics and essential oil led to a significant decrease in these parameters. Similar to previous studies, our results showed that serum total protein and albumin were not affected by dietary supplements 41 , 42 . Furthermore, our results have similarities with Santoso et al 43 who reported that adding probiotics lowered levels of ALT enzyme compared with the control treatment.…”
Section: Discussionsupporting
confidence: 92%
“…The hypocholesterolemic in the blood may be due to some components of essential oils that inhibit 3-hydroxy-3-methylglutaryl coenzyme A reductase, which is the enzyme responsible for cholesterol synthesis 39 . It has been reported that probiotics and EO significantly decrease serum LDL levels 40 , 41 . In this study, adding probiotics and essential oil led to a significant decrease in these parameters.…”
Section: Discussionmentioning
confidence: 98%